Integrating Palliative Care Into a Neurosurgical Intensive Care Unit (NS-ICU): A Quality Improvement (QI) Project. (June 2022) - Poi, Choo Hwee; Koh, Mervyn Yong Hwang; Koh, Tessa Li-Yen; Wong, Yu-Lin; Mei Ong, Wendy Yu; Gu, Chunguang; Yow, Fionna Chunru; Tan, Hui Ling
Objectives: We conducted a pilot quality improvement (QI) project with the aim of improving accessibility of palliative care to critically ill neurosurgical patients. Methods: The QI project was conducted in the neurosurgical intensive care unit (NS-ICU). Prior to the QI project, referral rates to palliative care were low. The ICU-Palliative Care collaborative comprising of the palliative and intensive care team led the QI project from 2013 to 2015. The interventions included engaging key stake-holders, establishing formal screening and referral criteria, standardizing workflows and having combined meetings with interdisciplinary teams in ICU to discuss patients' care plans. The Palliative care team would review patients for symptom optimization, attend joint family conferences with the ICU team and support patients and families post-ICU care. We also collected data in the post-QI period from 2016 to 2018 to review the sustainability of the interventions. Results: Interventions from our QI project and the ICU-Palliative Care collaborative resulted in a significant increase in the number of referrals from 9 in 2012 to 44 in 2014 and 47 the year later. The collaboration was beneficial in facilitating transfers out of ICU with more deaths outside ICU on comfort-directed care (96%) than patients not referred (75.7%, p < 0.05). Significantly more patients had a Do-Not-Resuscitation (DNR) order upon transfer out of ICU (89.7%) compared to patients not referred (74.2.%, p < 0.001), and had fewer investigations in the last 48 hours of life (p < 0.001). Per-day ICU cost was decreased for referred patients (p < 0.05). Conclusions: Multi-faceted QI interventions increased referral rates to palliative care. Referred patients had fewer investigations at the end-of-life and per-day ICU costs.